Analisis Kesalahan Berbahasa pada Teks Laporan Hasil Observasi Siswa Kelas 8 SMPN 20 Tasikmalaya berdasarkan Kategori Fonologi - Neng Elis Handayani; Rifa Fauziah Salma; Lisa Herlina; Ai Siti Nurjamilah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
When conducting research, many language errors were found in the writing of observation reports in class 8A of SMP 20 Tasikmalaya. The approach used is descriptive qualitative combined with language error analysis theory. Research data on student learning outcomes is in the form of 36 texts. Data was collected using interview and observation techniques. The research results showed that there were 25 students who made mistakes and 11 students who did not make mistakes, especially at the phonological level. The purpose of this research is to determine the level of success of students in writing observation report texts.